KAJIAN PROGRAM PEMBINAAN OLAHRAGA BADAN PEMBINA OLAHRAGA MAHASISWA (BAPOMI) PROVINSI JAWA TENGAH (Journal of Sport Coaching and Physical Education, 2016)
The pattern of Badan Pembina Olahraga Mahasiswa (Bapomi) Central Java Province development programs is very weak in implementation and has not become a national sport in the guidance subsystem. BAPOMI development patterns still oriented coaching is done by universities and the parent organization of the sport (Pengprov). Bapomi still weak from the SWOT and CIPP analysis. Sports development in Indonesia has not fully focused one direction that is still divided into track clubs and Educational track. that can makes athletes College development programs for Athlete by BAPOMI or elements of the college will be very weak. Bapomi must have Preparation of the work program, Strategic plans and regulation of college Athlete Development, Bapomi need a local regulations on the development and guidance of sports as an amplifier and a legal framework for the development of sports in college, Before the advent of PPLM from local budgets adjusted by mapping the featured sports in college. So Bapomi must have the role of higher education as a subsystem of national sports Development.